High-entropy alloys by mechanical alloying: A review - Vaidya, Mayur; Muralikrishna, Garlapati Mohan; Murty, Budaraju Srinivasa (Journal of materials research, 2019)
Mechanical alloying (MA) followed by sintering has been one of the most widely adopted routes to produce nanocrystalline high-entropy alloys (HEAs). Enhanced solid solubility, room temperature processing, and homogenous alloy formation are the key benefits provided by MA. Spark plasma sintering has largely been used to obtain high-density HEA pellets from milled powders. However, there are many challenges associated with the production of HEAs using MA, which include contamination during milling and high propensity of oxidation. The present review provides a comprehensive understanding of various HEAs produced by MA so far, with the aim to bring out the governing aspects of phase evolution, thermal stability, and properties achieved. The limitations and challenges of the process are also critically assessed with a possible way forward. The paper also compares the results obtained from high-pressure torsion, another severe plastic deformation technique.